2021
DOI: 10.3390/f12101394
|View full text |Cite
|
Sign up to set email alerts
|

How Can Local and Regional Knowledge Networks Contribute to Landscape Level Action for Tree Health?

Abstract: Forests worldwide are facing increasing pressures, with human travel and trade assisting the spread of pests and diseases. Climate change is likely to enhance the negative impacts of pests and diseases, which cause global declines and local extinctions. In this research we focus on three local and regional knowledge networks in the UK concerned with pests and diseases to explore to what extent the networks raise awareness and encourage other actions in their members, and identify what roles social capital and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The second period of co-design was more varied and creative in the tools and techniques employed. A national survey elicited further views on how far land manager networks might provide collaborative working for tree health at a landscape scale and how this might be integrated into policy design (O'Brien et al, 2021). Deliberative workshops included exercises involving card sorting, scenario and story-telling techniques to discuss high level design issues, e.g., the balance between regulation, incentive, advice and guidance, as well as more detailed consideration of the range of policy options.…”
Section: Identifying and Using Different Methods Tools And Techniquesmentioning
confidence: 99%
“…The second period of co-design was more varied and creative in the tools and techniques employed. A national survey elicited further views on how far land manager networks might provide collaborative working for tree health at a landscape scale and how this might be integrated into policy design (O'Brien et al, 2021). Deliberative workshops included exercises involving card sorting, scenario and story-telling techniques to discuss high level design issues, e.g., the balance between regulation, incentive, advice and guidance, as well as more detailed consideration of the range of policy options.…”
Section: Identifying and Using Different Methods Tools And Techniquesmentioning
confidence: 99%
“…In contrast, Müller and Job (2009) found that knowledge about native spruce bark beetles (Ips typographus) was strongly associated with decreased support to manage forests in response to them. Specific to forest management, knowledge of management projects, terms, and processes positively influenced support for disturbance-based management treatments (O'Brien et al 2021;Shindler and Mallon 2006). Thus, the application of knowledge and familiarity related to EAB infestations seem warranted.…”
Section: Influencing Visitor Preferences and Displacement Through Inf...mentioning
confidence: 99%